Cardiac sarcoidosis: from diagnosis to treatment - Kysperska, Kristyna; Kuchynka, Petr; Palecek, Tomas (Biomedical papers, 2021)
Sarcoidosis is a systemic granulomatous disease of unknown cause. Its clinical presentations are heterogeneous and virtually any organ system can be affected, most commonly lungs. The manifestations of cardiac sarcoidosis (CS) are heterogenous depending on the extent and location of the disease and range from asymptomatic forms to life-threatening arrhythmias as well as to progressive heart failure. Cardiac involvement is associated with a worse prognosis. The diagnosis of CS is often challenging and requires a multimodality approach based on current international recommendations. Pharmacological treatment of CS is based on administration of anti-inflammatory therapy (mainly corticosteroids), which is often combined with heart failure medication and/or antiarrhythmics. Nonpharmacological therapeutic approaches in CS cover pacemaker or defibrillator implantation, catheter ablations and heart transplantation. This review aims to summarize the current understanding of CS including its epidemiology, etiopathogenesis, clinical presentations, diagnostic approaches, and therapeutic possibilities.
Keywords: granulomas; FDG-PET/CT; conduction disorders; ventricular arrhythmias; heart failure